Pengaruh Customer Experience dan Brand Trust Terhadap Customer Loyalty Pada Produk Implora di Aster Kosmetik Malang - Nabila Chika Amanda, Firsa; Maskan, Mohammad; Hadi, Musthofa (PENG: Jurnal Ekonomi dan Manajemen, 2025)
For companies, customer experience is very important because it can influence customer perceptions. Another factor is brand trust, whichh describes the extent to which consumers feel confident in a product. This research aims to find out how customer experience and brand trust influence customer loyalty. This research is quantitative research with the variables customer experience, brand trust and customer loyalty. Purposive sampling technique was used as a data collection technique through questionnaires and as many as 100 respondents. Data analysis uses multiple linear regression analysis. Based on the results of partial simultaneous hypothesis testing, it shows that customer experience and brand trust have a positive and significant influence on customer loyalty to Implora products at Aster Cosmetics Malang. Based on the results of this research, it can be concluded that positive customer experience and good brand trust are one of the reasons for customer loyalty.